Practitioner Survey from human rights ontology (OntoRights) study - Lindeberg, Jöran (Stockholm University, 2022)
These tables include aggregated and anonymised results from human rights practitioners who completed a survey about the kind of information that a database about human rights violations documentation should be able to represent. Links to the questionnaire were distributed during 4-26 April 2022. 13 people completed the questionnaire.
More information about this project can be found on OntoRights website: https://joranl.github.io/human-rights-ontology/

The pdf-file contains the complete questionnaire in English and Spanish. (This is a paper-version, however, all participants used an online form).
The ods-file shows the results from the survey and the calculations behind them.
The odt-file shows these same results, but also in the last two columns map que questions to an estimation by the author of to what degree the question can be considered represented by OntoRights
Keywords: Computer and Information Science; human rights violations documentation; survey data; Computer and Information Sciences; Data- och informationsvetenskap (datateknik)